Benthic invertebrates in the Wadden Sea form a stable community characterized by facilitating relationships - Mark Rademaker; Paula de laBarra; Anieke vanLeeuwen; Allert I. Bijleveld (Ecosphere)
Abstract Entire tidal food webs rely on the presence and productivity of benthic invertebrates. These invertebrates recycle nutrients, decompose organic matter, and function as food for myriad species at higher trophic levels. The interactions between benthic invertebrate species also play an important role in shaping the ecological functioning of these ecosystems. Here, we used a deep‐learning species distribution model to characterize the interspecific interactions occurring in an intertidal benthic invertebrate community while accounting for abiotic factors. The data include >30,000 samples collected between 2008 and 2020, over a spatial grid of more than 2400 km2 in the Wadden Sea. The benthic invertebrates in the Wadden Sea were shown to form a stable community where species engage in relatively few strong interactions in a larger network of weak interactions. This corroborates classical theory on stability–connectivity relations. We provide a stepping stone for species‐specific analysis by showing that the numbers of interaction link to functional species traits. However, the biological interpretation of these links remains open. We conclude that rather than posing a catch‐all solution for improving our understanding of benthic invertebrate communities, our approach provides a baseline interaction mapping tool and starting point for more targeted experiments to elucidate underlying mechanisms.